Ordoliberalism goes China? A comparison of recent developments in EU and chinese competition law considering the digital economy - Anselm Küsters (Constitutional Political Economy, 2023)
The rapidly advancing digitalisation of the global economy, particularly the emergence of quasi-monopolists with the ability to define the rules of the game, poses numerous challenges to competition law as it is now practised worldwide. The European Union and China, in particular, have recently taken up these challenges with far-reaching reforms of their respective competition law regimes. This paper analyses these reforms and trends from a critical perspective informed by ordoliberalism, one of the arguably most influential schools of competition thought. First, the core ideas of the early Freiburg School on competition are distilled. The subsequent sections compare this ideal type with current developments in EU and Chinese competition law. The discussion of similarities and differences shows that both reform agendas suffer from similar problems connected to the rule of law and suggests that a modernised ordoliberal competition law approach must be guided not only by substantive but also by procedural aspects.
Keywords: B25; K21; O38; P51; 330; Ordoliberalism; EU; China; Competition Law; Rule of Law; Techlash